2010
DOI: 10.1007/s00217-010-1261-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-photoaging effect of fermented rice bran extract on UV-induced normal skin fibroblasts

Abstract: Rice bran contains various polyphenolic compounds with anti-oxidative activities, and it has long been known to inhibit melanogenesis. Cofermentation of rice bran with Lactobacillus rhamnosus and Saccharomyces cerevisiae significantly reduced the melanin synthesis of the resulting extract to B16F1 melanoma cells. However, anti-aging and anti-inflammatory effects of these fermented rice bran extracts (FRBEs) were not investigated. The objective of this work was to investigate the ability of FRBE to protect fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Previous studies have shown that rice bran fermented with Saccharomyces cerevisiae has anti-stress and anti-fatigue effects [16]. Furthermore, polysaccharide extracts of rice bran fermented with Lentinus edodes has anti-cancer properties, and water extracts of FRB which were stimulated by S. cerevisiae and Lactobacillus rhamnosus had an anti-photoaging effect [17,18]. FA and fractionized phenolic acid from rice bran exhibited hypoglycemic effects in a type 2 diabetic mice model [19].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that rice bran fermented with Saccharomyces cerevisiae has anti-stress and anti-fatigue effects [16]. Furthermore, polysaccharide extracts of rice bran fermented with Lentinus edodes has anti-cancer properties, and water extracts of FRB which were stimulated by S. cerevisiae and Lactobacillus rhamnosus had an anti-photoaging effect [17,18]. FA and fractionized phenolic acid from rice bran exhibited hypoglycemic effects in a type 2 diabetic mice model [19].…”
Section: Introductionmentioning
confidence: 97%
“…A bran extract subjected to enzymatic fermentation has been evaluated on cultivated keratinocytes and in vitro-reconstructed skin, serving as a protective screen against UV-B radiation (Santa-Maria, Revilla et al 2010). Similarly, another bran fermented extract, obtained from Lactobacillus rhamnosus and Saccharomyces cerevisiae, has protected fibroblasts from in vitro exposure to UV-B rays (Seo, Jung et al 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent studies have reported that these extracts exert a number of biological effects on animal cells, including the following: enhancement of human natural killer cell activity (Ghoneum 1998); anti-photoaging effects in human fibroblasts (Seo et al 2010); and antiinflammatory effects in mice (Akihisa et al 2000). However, there is no report concerning the biological effects of RBE on MSCs.…”
Section: Introductionmentioning
confidence: 99%